Innovation: the bright side of common ownership? - Anton, M; Ederer, F; Giné, M; Schmalz, MC (INFORMS, 2024)
Firms have inefficiently low incentives to innovate when other firms benefit from their inventions and the innovating firm therefore does not capture the full surplus of its innovations. We show that common ownership of firms mitigates this impediment to corporate innovation. By contrast, without technological spillovers, innovation has the effect of stealing market share from rivals; in that case, more common ownership reduces innovation. Empirically, the association between common ownership and innovation inputs and outputs decreases with product market proximity and increases with technology proximity. The sign and magnitude of the overall relationship between common ownership and corporate innovation thus varies considerably across the universe of firms depending on their relative proximity in technology and product market space. These results persist if we use only variation from BlackRock's acquisition of BGI. Our results inform the debate about the welfare effects of increasing common ownership among U.S. corporations.